Personalities, Cyber Activities, and Adolescent Cyber Delinquency - O, SooHyun (Crime & delinquency, 2025)
This study examines how crime propensity characteristics relate to cyber delinquency directly and indirectly, through crime opportunity. In doing so, it considers propensity by way of different aspects of personality and crime opportunity in the form of a comprehensive set of online activities. Both the direct and indirect relationships are modeled using path analysis in MPlus with the data from 2,015 students from schools in South Korea. Findings suggest several personality traits and online computer activities are significantly related to cyber delinquency. Moreover, these activities often mediate the effects of propensity as measured by personality factors. Overall, findings support the idea that individual enduring propensities and online activities work in tandem to predict adolescent cyber offending.